Odonate Nymphs: Generalist Predators and their Potential in the Management of Dengue Mosquito, Aedes aegypti (Diptera: Culicidae) - Waseem Akram; Hafiz Azhar Ali-Khan (Tehran University of Medical Sciences, 2016)
Background: Dengue is amongst the most serious mosquito-borne infectious disease with hot spots in tropical and subtropical parts of the world. Unfortunately, no licensed vaccine for the disease is currently available in medicine markets. The only option available is the management of dengue vector mosquito, Aedes aegypti (Diptera: Culicidae). Method: Predatory potential of five odonate nymphs namely Anax parthenope, Bradinopyga geminate, Ischnura forcipata, Rhinocypha quadrimaculata, and Orthetrum sabina were evaluated against the 4th instar larvae of the dengue vector mosquito, Aedes aegypti, under laboratory conditions. The consumption of the mosquito larvae was evaluated at three water volume levels viz., 1 liter, 2 liter and 3 liter. Results: The number of Ae. aegypti larvae consumed varied significantly among the five species, and at different levels of water volume (P< 0.01). However, the interaction between odonate nymphs and the water volumes was statistically non-significant (P> 0.05). Ischnura forcipata consumed the highest number of Ae. aegypti larvae (n=56) followed by A. parthenope (n=47) and B. geminate (n=46). The number of larvae consumed was decreased with increasing search area or water volume, and the highest predation was observed at 1-liter water volume. Conclusion: The odonate nymphs could be a good source of biological agents for the management of the mosquitoes at larval stages.